2006
DOI: 10.1104/pp.106.085944
|View full text |Cite
|
Sign up to set email alerts
|

A Heteromeric RNA-Binding Protein Is Involved in Maintaining Acrophase and Period of the Circadian Clock

Abstract: The RNA-binding protein CHLAMY1 from the green alga Chlamydomonas reinhardtii consists of two subunits. One (named C1) contains three lysine homology motifs and the other (named C3) has three RNA recognition motifs. CHLAMY1 binds specifically to uridine-guanine-repeat sequences and its circadian-binding activity is controlled at the posttranslational level, presumably by time-dependent formation of protein complexes consisting of C1 and C3 or C1 alone. Here we have characterized the role of the two subunits wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 41 publications
2
88
0
Order By: Relevance
“…Both light conditions altered the levels of these transcripts, but in several cases the changes in transcript abundance were modest (1.5-to 3-fold). An exception was noted for the C3 subunit of the RNA binding protein CHLAMY1; altered expression of this protein causes phase shifts in circadian responses (Iliev et al, 2006). We observed an ;15-fold increase in the C3 transcript after the cells were exposed to 30 min of either blue or red light, demonstrating that the gene encoding C3 belongs to a group of rapidly induced genes such as VVD in Neurospora; a disruption in VVD also causes phase shifts of circadian rhythms (Heintzen et al, 2001;Lewis et al, 2002).…”
Section: Blue and Red Light Cause A Similar Change In Gene Expressionmentioning
confidence: 80%
See 3 more Smart Citations
“…Both light conditions altered the levels of these transcripts, but in several cases the changes in transcript abundance were modest (1.5-to 3-fold). An exception was noted for the C3 subunit of the RNA binding protein CHLAMY1; altered expression of this protein causes phase shifts in circadian responses (Iliev et al, 2006). We observed an ;15-fold increase in the C3 transcript after the cells were exposed to 30 min of either blue or red light, demonstrating that the gene encoding C3 belongs to a group of rapidly induced genes such as VVD in Neurospora; a disruption in VVD also causes phase shifts of circadian rhythms (Heintzen et al, 2001;Lewis et al, 2002).…”
Section: Blue and Red Light Cause A Similar Change In Gene Expressionmentioning
confidence: 80%
“…The complete pKP39 sequence is presented in Supplemental Data Set 2 online. The mutant strain SAG73.72:acry1A was transformed with the AhdI-linearized pKP39 using the autolysin method as described earlier (Iliev et al, 2006). Cells were grown on Tris-acetate-phosphate agar medium (Harris, 1989) containing 20 µg/mL hygromycin B.…”
Section: Complementation Of the Acry1a Mutant By Transformation With mentioning
confidence: 99%
See 2 more Smart Citations
“…The O. tauri and C. reinhardtii genomes lack additional PRR-like genes and do not have recognizable ELF3, ELF4, GI, or ZTL homologs (Matsuo et al, 2008;Corellou et al, 2009). In addition, forward genetic studies in C. reinhardtii have demonstrated that genes without obvious homologs in higher plants are essential for normal clock function in this species (Iliev et al, 2006;Matsuo et al, 2008). It will be fascinating to learn the mechanistic similarities and differences between the clocks of the green algae and those of the land plants.…”
Section: The Beginning Of Timingmentioning
confidence: 99%